School reactivation programs after disaster: could teachers serve as clinical mediators? - (:unkn) unknown (W B SAUNDERS CO, 2003)
Despite the numerous advantages in implementing school-based interventions after a trauma or disaster, particularly interventions mediated by teachers, only a few articles have been published on this subject. This article reviews the relevant literature and offers a conceptual framework for implementing teacher-mediated mental health clinical intervention programs among school-age children. The authors propose a process that mental health professionals and teachers may need to go through and the adaptation of roles required to be placed in an educational-therapeutic position within a school reactivation program. The authors describe such a program carried out in the city of Adapazari, Turkey, after the 1999 earthquakes in which estimates of posttraumatic stress disorder decreased from 30% to 18% within 4 weeks.
Keywords: POSTTRAUMATIC-STRESS-DISORDER; MENTAL-HEALTH-SERVICES; PSYCHOSOCIAL INTERVENTION; MISSILE ATTACKS; FOLLOW-UP; CHILDREN; TRAUMA; ADOLESCENTS; EARTHQUAKE; SYMPTOMS